Effects of cereals as agro-ecological service crops and no-till on organic melon, weeds and N dynamics. Issue 4 (2nd October 2019) - Campanelli, Gabriele; Testani, Elena; Canali, Stefano; Ciaccia, Corrado; Leteo, Fabrizio; Trinchera, Alessandra
ABSTRACT: In a two-year field experiment undertaken in Central Italy, different agro-ecological service crops (ASCs), terminated by the no-till roller crimper technology before organic melon production ( Cucumis melo L.), were evaluated by assessing soil-plant N dynamics, weed management and crop performance, and by comparing with a tilled control without ASC. The ASCs ( Poaceae, i.e. rye, barley, wheat, spelt and their mixture), were characterised in terms of aboveground biomass, N uptake, C : N ratio and degradation rate. During the melon growth cycle, soil mineral N (SMN), weed density and biomass were measured and the design of trial included weeded and unweeded plots. The yield and concentrations of soluble solids of the melon was measured. The ASC mulches differed in their N supply capacity and degradation rate. Rye and spelt were the best in terms of weed control, with approximately 80% lower weed density and weed biomass for either rye or spelt compared with the control. Wheat was the least effective against weeds, but it enhanced SMN. Melon yields were similar in plots with spelt and rye, weeded and unweeded treatments, but were reduced in the unweeded control (−58.5%) and barley treatment (−41.2%), compared with the respective weeded treatments. The low melon yield in the plots with rye suggested a negative allelopathic rye-melon interaction. The results highlighted that the ASCs were able to regulate, to different extents, the agro-ecosystem interactions.